Compression of the clay soils of non-destructed and destructed structure - Alikonis, Antanas (Journal of Civil Engineering and Management, 1997)
Clay soils have their structural links according to their geological conditions. Compression increases when the soil structural lines are destructed. Even if the density of the soils of distructed structure reaches the density of natural soils, though they get deformed differently under loading. Sometimes it is necessary to have equivalent compression of the soils of destructed and natural structure in construction.The article presents mathematical dependency on how to count a porosity factor of the soils of destructed structure, with its help relative deformations under a given loading come up with relative deformation of natural soils, using dependency of compression porosity factor of structurally rigid soils upon loading in a semi-logarithmic scale. Experimental research into Lithuanian limnoglacial clay soils has showed that increase in the assessment of the initial porosity factor is followed by an increase in difference between the compression of non-destructed and destructed soils. Experimentally obtained and calculated (according to formula 15) results show that, for example, under the loading of 0,2 MPa, decrease in the assessment of the initial porosity factor is followed by a decrease in difference between the assessments of the initial porosity factor of destructed structure, giving deformations equivalent to those of natural soils. The difference which occured after experimentally obtained and calculated results were compared-from 2% to 10%.The decrease in difference shows that an increase in soil density is followed by a decrease in sensitivity of destructure of its natural structure. The initial porosity factor of the soils of destructed structure, calculated according to formula (15), enables us to have deformations equivalent to those of natural soils and it is provided for the loading used in formula (15). Changes in loading will be followed by changes in the assessment of the initial porosity factor calculated according to formula (15).The increase in loading is followed by an increase in the initial assessment of the porosity factor. It shows that an increase in loading is followed by an increase in the degree of destruction of structural links of natural soils and its nature of compression comes up with the compression of the soils of destructed structure. Structural rigidity of soil can be determined by intersection of lines AC and CD (Fig 1).After the natural structure of clay soils has been destructed, part of its structural rigidity remains. Experimental research shows that there is a short interval AB a small pitch (Fig 2) in a compression curve of limnoglacial kneaded up clay indicating the remaining structural links. According to experimental research, in comparison to natural soils, structural rigidity of the clay soils of destructed structure (kneaded up clay soils) forms a very small part. Therefore when working out engineering tasks connected with construction, we shoned accept that the compression curve of the clay soils of destructed (kneaded up) structure in a semi-logarithmic scale is a line, with its beginning at point A (Fig 2). It indicates that deformation of destructed soils begins with the initial loading (Fig 1, line 3), whereas considerable deformation of natural soils begins under the loading higher than the structural rigidity of the soil.Nesuardytos ir suardytos sandaros molingojo grunto suspaudžiamumasSantrauka. Molingieji gruntai del jų geologinių susiklostymo sąlygų turi struktūrinius ryšius. Suardžius grunto struktūrinius ryšius padidėja suspaudžiamumas. Suardytos sandaros gruntas, nors ir sutankintas iki tankumo, prilygstančio natūralaus grunto tankumui, veikiant apkrovai deforrnuojasi skirtingai. Statybose pasitaiko atvejų, kai reikia turėti vienodą susispaudžiamumą esant grunto suardytai ir natūraliai sandarai.Naudojant molingojo grunto su struktūriniu stiprumu kompresines poringumo koeficiento priklausomybes nuo apkrovos pusiau logaritminiame mastelyje, straipsnyje pateikta matematinė priklausomybė (15) apskaičiuoti suardytos sandaros grunto poringumo koefieientui, kuriam esant santykinės deformacijos esant tarn tikrai apkrovai prilygsta natūralaus grunto santykinėms deformacijoms.Eksperimentiniai Lietuvos limnoglacialinių molių tyrimai parodė, kad suspaudžiamumo skirtumas tarp suardytos ir nesuardytos sandaros grunto didėja, didėjant pradinio poringumo koeficiento vertei.Eksperimentinių tyrimų ir apskaičiuoti pagal (15) formulę rezultatai rodo, kad, pavyzdžiui, esant 0,2 MPa apkrovai skirtumas tarp suardytos sandaros pradiniq poringumo koeficiento verčių, duodančių vienodas deformacijas, kaip ir natūralaus grunto, mažėja mažėjant pradinei poringumo koeficiento vertei. Skirtumas, gautas sugretinus eksperimento ir skaičiavimo rezultatus, yra nuo 2 iki 10%. Skirtumo mažėjimas rodo, kad didejant grunto tankumui mazėja jautrumas natūralios struktūros suardymui.Apskaičiuotas pagal (15) formulę suardytos sandaros grunto pradinis poringumo koeficientas, kuriam esant turėsime tokias pat, kaip natūralaus grunto, deformacijas, yra skirtas apkrovai, naudotai (15) formulėje. Keičiantis apkrovai keisis ir apskaičiuota pagal (15) formulę pradinio poringumo koeficiento vertė. Didėjant apkrovai didėja ir pradinės poringumo koeficiento vertės, apskaičiuotos pagal (15) formulę. Tai rodo, kad didėjant apkrovai didėja natūralaus grunto struktūriniq ryšių suardymo laipsnis, ir jo suspaudžiamumo pobūdis panašus į suardytos sandaros grunto suspaudžiamumą.Article in Russian.First Published Online: 26 Jul 2012